Evaluasi kualitas perairan Sungai Siak di wilayah Kota Pekanbaru berdasarkan kandungan nitrat, posfat dan kelimpahan diatom - Syifa Murtaja; Bintal Amin; Thamrin Thamrin (Pelantar Press, 2017)
Sungai Siak waters is most commonly used by communities Pekanbaru for various activities such as water transportation, fisheries, agriculture, household, industrial and others. While these activities generate waste in the form of partial discharges would enter the river. The purpose of this study was to evaluate the quality of the waters of the Sungai Siak in the city of Pekanbaru based on the content of nitrate and phosphate. The results of measurements of nitrate in the Sungai Siak ranged from 0.2343 to 0.2771 mg/l. Nitrate highest value at Station 4 is 0.3384 mg/l and the lowest at Station 1 is worth 0.2010 mg/l. The content of phosphate in the Siak River which ranged from 1.3932 to 1.5170 mg/l. Great relationship between nitrate with an abundance of diatoms were calculated by correlation coefficient (r) was 0.707 showed a strong association.Great relationship between phosphate with an abundance of diatoms were calculated by correlation coefficient (r) was 0.728 showed a strong association.